Sex Differences in Depression and Anxiety - Pavlidi, P.; Kokras, N; Dalla, C (Curr Top Behav Neurosci, 2023)
Depression and anxiety disorders carry a tremendous worldwide burden and emerge as a significant cause of disability among western societies. Both disorders are known to disproportionally affect women, as they are twice more likely to be diagnosed and moreover, they are also prone to suffer from female-specific mood disorders. Importantly, the prevalence of these affective disorders has notably risen after the COVID pandemic, especially in women. In this chapter, we describe factors that are possibly contributing to the expression of such sex differences in depression and anxiety. For this, we overview the effect of transcriptomic and genetic factors, the immune system, neuroendocrine aspects, and cognition. Furthermore, we also provide evidence of sex differences in antidepressant response and their causes. Finally, we emphasize the importance to consider sex as a biological variable in preclinical and clinical research, which may facilitate the discovery and development of new and more efficacious antidepressant and anxiolytic pharmacotherapies for both women and men.
Keywords: *Covid-19; *Depression/drug therapy/epidemiology; antidepressants; Antidepressive Agents/therapeutic use; anxiety; Anxiety Disorders/epidemiology/drug therapy; Depression; Female; Humans; Male; Sex Characteristics; Sex differences; stress